Evidence of half-metallicity at the BiFeO3(001) surface. (22nd March 2023) - Jena, Soumyasree; Datta, Sanjoy
Abstract : Evidence of half-metallicity at the BiFeO3 (001) surface has been found. Half-metals are considered to be one of the most promising candidate for efficient spin-injection and detection processes in spintronic devices. Abstract : Spintronic devices require spin-polarized electrons for efficient performance, and half-metals are promising to provide the required platform to achieve it. However, a common problem of most of the existing bulk half-metallic materials is that the surface, especially the (001) surface, does not retain the half-metallic characteristics. Recently, half-metallicity has been predicted in a bulk tetragonal BiFeO3 structure. In this study, we investigated the electronic properties and thermodynamic stability of tetragonal BiFeO3 (001) surfaces using first-principles calculations and found evidence of half-metallicity along with spin-polarized two-dimensional hole gas (2DHG) at the surface of the most stable structure. Furthermore, we have found that the surface electronic properties and thermodynamic stability are quite sensitive with respect to the nature of surface termination. The FeO2 -terminated surface is found to be energetically more stable compared to the BiO-terminated surface. Interestingly, half-metallic states have been observed at the FeO2 -terminated surface, while the BiO-terminated surface turns out to be metallic.